2020
DOI: 10.1002/agj2.20258
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability evaluation of ORYZA (v3) for single‐cropped rice under different establishment techniques in eastern China

Abstract: The ORYZA (v3) rice model is the most exhaustive representation of the available knowledge on rice (Oryza sativa L.) growth and development and has become an integrated rice modelling tool suitable for different scenarios according to the demands of users. A 3‐yr field experiment was conducted under potential production conditions for single‐cropped rice during 2011–2013 in Jiangsu Province in eastern China. The simulation performance of ORYZA (v3) with respect to the growth and development of different rice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(51 reference statements)
5
8
0
Order By: Relevance
“…The figure shows that LAI has the lowest nRMSE, ranging from about 2-26%, followed by dry biomass of green leaves, ranging from about 5-27%, and dry total aboveground biomass, ranging from about 11-30%. These results are consistent with previous research, which found nRMSE values ranging from 7 to 34% for dry bisomass of total aboveground stems, panicles, green leaves, and LAI for both calibration and validation sets (Cao et al 2017, Yuan et al 2017, Xu et al 2018, Lu et al 2020. Meanwhile, Li et al (2016) found LAI (16-70%) and green leaves (14-70%) have wider nRSME ranges, while total aboveground dry biomass (4-20%), panicles, (3-18%), and stems (1-38%) have smaller ranges across eleven rice varieties.…”
Section: Evaluation Of the Oryza (V3) Performancesupporting
confidence: 93%
See 3 more Smart Citations
“…The figure shows that LAI has the lowest nRMSE, ranging from about 2-26%, followed by dry biomass of green leaves, ranging from about 5-27%, and dry total aboveground biomass, ranging from about 11-30%. These results are consistent with previous research, which found nRMSE values ranging from 7 to 34% for dry bisomass of total aboveground stems, panicles, green leaves, and LAI for both calibration and validation sets (Cao et al 2017, Yuan et al 2017, Xu et al 2018, Lu et al 2020. Meanwhile, Li et al (2016) found LAI (16-70%) and green leaves (14-70%) have wider nRSME ranges, while total aboveground dry biomass (4-20%), panicles, (3-18%), and stems (1-38%) have smaller ranges across eleven rice varieties.…”
Section: Evaluation Of the Oryza (V3) Performancesupporting
confidence: 93%
“…Li et al (2016) also discovered a high nRMSE for dead leaves of up to 105% for the NSICRc158 variety. The dead leaves are the least evaluated traits in many studies (Cao et al 2017, Yuan et al 2017, Lu et al 2020.…”
Section: Evaluation Of the Oryza (V3) Performancementioning
confidence: 99%
See 2 more Smart Citations
“…These studies dealt with many factors, including the rice cultivar, nitrogen management, water scheme, planting density, seedling age, and atmospheric CO 2 concentration (Boling et al., 2011; Bouman et al., 2007; Li et al., 2013). In addition, ORYZA series models have been used in transplanted (Bouman & van Laar, 2006; Jing et al., 2008; Li et al., 2013) and direct‐seeded rice systems (Boling et al., 2011; Lu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%